2019
DOI: 10.1093/ajcn/nqy324
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of satiety gut hormones increases appetitive behavior after curative esophagectomy for esophageal cancer

Abstract: Background Reduced appetite and weight loss are common after esophagectomy (ES), and this cohort demonstrates an exaggerated postprandial satiety gut hormone response. Satiety gut hormones modulate food reward, resulting in reduced energy intake. Objectives This study aimed to determine the effect of satiety gut hormone modulation by measuring the effect of the somatostatin analog octreotide on appetitive behavior among patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In fact, indirect inhibition of GLP-1 secretion via sc injection of octreotide, a somatostatin analog, enhances computer mouse clicks for chocolate rewards in individuals who underwent RYGB surgery but not in obese nonoperated controls, suggesting that RYGB surgery influences the effects of GLP-1 signaling on food-motivated responses [99]. Similarly, patients who underwent esophagectomy for cancer present elevated postprandial levels of GLP-1 relative to healthy control subjects and also present an increase in computer mouse clicks for chocolate following sc injection of octreotide, whereas healthy controls do not [100]. Thus, the extent to which GLP-1 signaling dampens food motivation is influenced by chronic metabolic status.…”
Section: Human Studiesmentioning
confidence: 99%
“…In fact, indirect inhibition of GLP-1 secretion via sc injection of octreotide, a somatostatin analog, enhances computer mouse clicks for chocolate rewards in individuals who underwent RYGB surgery but not in obese nonoperated controls, suggesting that RYGB surgery influences the effects of GLP-1 signaling on food-motivated responses [99]. Similarly, patients who underwent esophagectomy for cancer present elevated postprandial levels of GLP-1 relative to healthy control subjects and also present an increase in computer mouse clicks for chocolate following sc injection of octreotide, whereas healthy controls do not [100]. Thus, the extent to which GLP-1 signaling dampens food motivation is influenced by chronic metabolic status.…”
Section: Human Studiesmentioning
confidence: 99%
“…This is important to bear in mind when interpreting these findings and could feasibly underlie the lack of a positive effect with regards to body weight and composition with treatment. This is particularly pertinent as the studies describing an impact of short-acting Octreotide did demonstrate significant GLP-1 attenuation (27,28). There was no clear precedent on which to base the dosing in this clinical context.…”
Section: Discussionmentioning
confidence: 99%
“…This was a pilot study with the principal aim to determine feasibility of the protocol and effect size of the outcomes. When planning the study we used the PRT breakpoint as primary outcome as our previous data demonstrated that the difference in the response of matched pairs to Octreotide is normally distributed and is 88 with standard deviation of 47 (28). Were these values used, with a A c c e p t e d M a n u s c r i p t significance level of 0.05 and 0.9 power, then 5 participants would be needed to detect a difference with Octreotide LAR treatment.…”
Section: Power Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of the satiety gut hormone responses with a somatostatin analogue almost doubled ad libitum food intake [49]. Elliott et al showed that administration of octreotide in patients after esophagectomy led to attenuation of exaggerated postprandial satiety gut hormone responses which was associated with increased appetitive behavior toward a sweet-fat stimulus [71].…”
Section: New Promising Therapeutic Agentsmentioning
confidence: 99%